Vaccines and Immunotherapeutics for the Treatment of Malignant Disease - Joel F. Aldrich; Devin B. Lowe; Michael H. Shearer; Richard E. Winn; Cynthia A. Jumper; Ronald C. Kennedy (Clinical and Developmental Immunology)
The employment of the immune system to treat malignant disease represents an active area of biomedical research. The specificity of the immune response and potential for establishing long-term tumor immunity compels researchers to continue investigations into immunotherapeutic approaches for cancer. A number of immunotherapeutic strategies have arisen for the treatment of malignant disease, including various vaccination schemes, cytokine therapy, adoptive cellular therapy, and monoclonal antibody therapy. This paper describes each of these strategies and discusses some of the associated successes and limitations. Emphasis is placed on the integration of techniques to promote optimal scenarios for eliminating cancer.